Synthesis of (purin-6-yl)acetates and their transformations to 6-(2-hydroxyethyl)- and 6-(carbamoylmethyl)purines - Hasník, Zbyněk; Pohl, Radek; Klepetářová, Blanka; Hocek, Michal (Collection of Czechoslovak Chemical Communications, 2009)
A novel approach to the synthesis of (purin-6-yl)acetates was developed based on Pd-catalyzed cross-coupling reactions of 6-chloropurines with a Reformatsky reagent. Their reduction with NaBH4 and treatment with MnO2 gave 6-(2-hydroxyethyl)purines, while reactions with amines in presence of NaCN afforded 6-(carbamoylmethyl)purines. Mesylation of the 6-(2-hydroxyethyl)purines followed by nucleophilic substitutions gave rise to several 6-(2-substituted ethyl)purines. This methodology was successfully applied to the synthesis of substituted purine bases and nucleosides for cytostatic and antiviral activity screening. None of the compounds exerted significant activity.
Keywords: Structure-Activity Relationship; Purines; vztahy mezi strukturou a aktivitou; Financing, Organized; nukleosidy; puriny; financování organizované; Nucleosides